Proposição de modelo de análise de investimento tecnológico para implementação dos conceitos da indústria 4.0: investir em novos equipamentos ou Retrofit? - Souza, Victor Henrique Martins de (2022)
Investing in new equipment is one of the main challenges for Brazilian companies seeking to modernize their industrial park for the implementation of the concepts and technologies of Industry 4.0. The transformations and opportunities brought by this industrial revolution are important and necessary for companies that seek improvements in their productivity indicators, to be present in the market, with an emphasis on technology and innovation in manufacturing processes. With this intention, a question arises regarding the decision to invest in new equipment or to invest in the reform of existing equipment (Retrofit), with emphasis on their modernization. The objective of this research was to propose a technological investment analysis model to support the management of manufacturing processes in Brazilian industries in the decision about when to acquire new equipment or when to transform existing legacy equipment into modern systems for the adoption of Industry 4.0 concepts and technologies. The theoretical model proposed was evaluated by experts using the DELPHI method, and then refined. This work aims to contribute to the development of Technology and Innovation Management in Production Engineering.